2011
DOI: 10.1007/s13595-011-0095-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in forest structure and composition on Changbai Mountain in Northeast China

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 19 publications
6
26
0
Order By: Relevance
“…The estimates of carbon density for living trees and changes in this density over time are relatively reliable because: (1) the three permanent forest plots were selected because they were representative of typical forest types on Changbai Mountain (Dai et al 2011); (2) carbon contents in living trees were computed by using species-specific biomass equations developed from trees sampled in nearby forests; and (3) repeated measurements over time were used to quantify changes in forest biomass and carbon. Because a single 1-ha plot was used for each forest type, we were unable to compute the precision of carbon density estimates.…”
Section: Certainty Vs Uncertaintymentioning
confidence: 99%
“…The estimates of carbon density for living trees and changes in this density over time are relatively reliable because: (1) the three permanent forest plots were selected because they were representative of typical forest types on Changbai Mountain (Dai et al 2011); (2) carbon contents in living trees were computed by using species-specific biomass equations developed from trees sampled in nearby forests; and (3) repeated measurements over time were used to quantify changes in forest biomass and carbon. Because a single 1-ha plot was used for each forest type, we were unable to compute the precision of carbon density estimates.…”
Section: Certainty Vs Uncertaintymentioning
confidence: 99%
“…Changbai, northeastern China, which is one of the largest national forest reserves in China and covers an area of ∼ 1965 km 2 . The forest is dominated by tree species of Pinus koraiensis, Fraxinus mandshurica, Tilia amurensis, Acer mono and Quercus mongolica (Dai et al, 2011). There are no nearby sources at the MCB site and the predominant wind directions are from southwest to northwest, which could carry air pollutants from regional industrial and urbanized centers and northern China by long-range atmospheric transport (Fu et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…This special issue tends to cover broad disciplines/ approaches ranging from forest ecology to land use science, from ground observation to remote sensing/modeling, and from descriptive to analytical analysis. Dai et al (2011) investigated changes in forest structure and tree species composition, as well as population dynamics of the dominant tree species for two old-growth forests on Changbai Mountain from 1981 to 2010. They found that while stem density of the broad-leaved coniferous mixed forest at 740 m above sea level (asl) displayed almost no change, the total basal area increased from 36.2 to 46.5 m 2 ha −1 .…”
mentioning
confidence: 99%